2020
DOI: 10.3390/plants9091210
|View full text |Cite
|
Sign up to set email alerts
|

Field Survey and Resistance Occurrence to ALS-Inhibiting Herbicides in Glebionis coronaria L. in Tunisian Wheat Crops

Abstract: Glebionis coronaria (L.) Cass. ex Spach is a troublesome weed in cereal cropping systems in northern Tunisia. Recently, failures in controlling this weed have been reported by farmers. Field surveys and farmers interviews were conducted to highlight the potential causes of G. coronaria occurrence and the associated yield losses in wheat. Survey results revealed a significant correlation between farmers’ awareness of resistance occurrence and cultural practices, mainly sowing date and tillage, while G. coronari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
1
9
1
Order By: Relevance
“…The main reason was their broad-spectrum weed control at low rates. A previous survey, conducted in the same region, showed that florasulam was frequently used in a mixture with SAH to control G. coronaria in cereal crops ( Hada et al, 2020 ) while imazamox has never been applied on the weed to our knowledge.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The main reason was their broad-spectrum weed control at low rates. A previous survey, conducted in the same region, showed that florasulam was frequently used in a mixture with SAH to control G. coronaria in cereal crops ( Hada et al, 2020 ) while imazamox has never been applied on the weed to our knowledge.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies characterized P450-based metabolic cross-resistant individuals in L. rigidum and hypothesized that the genetic control was probably of polygenic and quantitative nature at the population level ( Yu and Powles, 2014b ; Han et al, 2021 ). Considering the complexity of metabolic herbicide resistance and the diversity and number of P450s in plants, we hypothesize that the differences observed in metabolism speed and metabolite amounts between the R1 and the R2 populations could be explained by herbicide and environmental selection pressures, particularly the history of herbicide applications in the fields where R populations were collected ( Yu and Powles, 2014b ; Hada et al, 2020 ). Owing to the genetic diversity of the weedy species, differences in the P450 activity and presence of other genes may be involved in the resistance of G. coronaria to imazamox, which can be observed even in different individuals of a single population as reported by Yu and Powles (2014b) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations